ROLE OF ORGANIC SPICES IN THE PRESERVATION OF SUB-SAHARAN AFRICAN TRADITIONAL FERMENTED BEVERAGES - Fapohunda, Stephen O; Animashaun , Oluwatoyin H. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
A review of the antimicrobial action of a few plant based natural products in Africa is reported . Spices play preservative and flavoring roles in food , fermented beverages and nutrition security in sub Saharan Africa, thereby increasing the shelf life . The emphasis on organic spices is underscored by their being Generally Recognized as Safe, GRAS, thus enhancing the wholesomeness of such consumption. The compatibility of fermenting microorganisms’ for various beverages is also noted. Volatile oils of black pepper, cloves, nutmeg, oregano and thyme have been shown to have antimicrobial activities against microorganisms.